Development and characterization of patient-derived xenograft models of colorectal cancer for testing new pharmacological substances - A. S. Goncharova; E. N. Kolesnikov; G. Yu. Egorov; A. Yu. Maksimov; A. N. Shevchenko; E. M. Nepomnyashchaya; D. Yu. Gvaldin; L. Z. Kurbanova; D. V. Khodakova; S. O. Kit; O. Yu. Kaymakchi; A. V. Snezhko (Бюллетень сибирской медицины, 2023)
The aim of the study was to create a patient-derived xenograft (PDX) model of human colorectal cancer and to determine its histologic and molecular characteristics, such as the status of KRAS, NRAS, and BRAF genes and the presence of microsatellite instability.Materials and methods. First generation xenograft models in vivo were created using tumors from patients with colorectal cancer (n = 4) and immunodeficient Balb/c Nude mice (n = 20); second, third, and fourth generation models were created in the same mouse line (n = 3 for each generation). A caliper was used to measure subcutaneous xenografts; their size was calculated by the ellipsoid formula. Cryopreservation involved immersing the samples in a freezing medium (80% RPMI 1640, 10% fetal bovine serum, 10% dimethyl sulfoxide (DMSO)) and storing them at –80 °C. The histologic analysis was performed according to the standard technique (preparation of paraffin blocks and staining of microsections with hematoxylin and eosin). Mutations in the KRAS, NRAS, and BRAF genes were determined by direct Sanger sequencing; microsatellite instability was determined by the fragment analysis at five loci: Bat-25, Bat-26, NR21, NR24, and NR27.Results. Stable, transplantable xenografts of colorectal cancer were obtained from two out of four patients. The average waiting time from the implantation to the growth of the first generation xenograft was 28 days. The latency phase after cryopreservation was comparable to that at the creation of the first generation PDX model. The model reproduced the histotype, grade and mutational status of the KRAS, NRAS, and BRAF genes, as well as microsatellite instability of the donor tumor.Conclusion. The developed model of human colorectal cancer was characterized in terms of growth dynamics, cryopreservation tolerance, and histologic and molecular genetic parameters.